Developing a Hospital Disaster Risk Management Evaluation Model - Abbasabadi Arab M; Khankeh HR; Mosadeghrad AM; Farrokhi M (Dove Medical Press, 2019)
Masoumeh Abbasabadi Arab,1 Hamid Reza Khankeh,1 Ali Mohammad Mosadeghrad,2 Mehrdad Farrokhi1 1Health in Emergency and Disaster Research Center, University of Social Welfare and Rehabilitation Sciences, Tehran, Iran; 2Management and Economics School of Public Health, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Hamid Reza KhankehHealth in Emergency and Disaster Research Center, University of Social Welfare and Rehabilitation Sciences, Kodakyar Street, Velenjak, Tehran, IranTel +98 21 2218 0160Fax +98 22 180 160Email hamid.khankeh@ki.sePurpose: Disasters are increasing worldwide and hospitals should be prepared to respond well to such disasters. An effective hospital disaster risk management program saves peoples’ lives, reduces damage to the hospital properties and assures hospital service continuity. This article aimed to develop and verify a Hospital Disaster Risk Management Evaluation model (HDRME).Methods: A mixed-method explanatory sequential approach was used to develop and verify the HDRME model. The first draft of the HDRME model was introduced through a comprehensive literature review of major databases (i.e., PubMed, Scopus, Web of Science, and Science Direct), using appropriate keywords. Furthermore, 18 in-depth individual interviews were conducted with well-known experts in DRM to identify more HDRME constructs, sub-constructs, and standards. Then, three rounds of Delphi were conducted with 22 experts in hospital disaster risk management to verify the proposed model.Results: The proposed HDRME consists of eight constructs, including seven enablers (management and leadership; risk assessment; planning; prevention and mitigation; preparedness; response, and recovery) and one result (key performance results). These constructs were further broken into 27 sub-constructs. The enablers and results scored 85% and 15% of the model’s total scores.Conclusion: A comprehensive conceptual framework for the evaluation of hospital disaster risk management was introduced and verified. Standards and measurable elements can be embedded in this conceptual model to measure a hospital’s preparedness in disasters and accordingly, corrective actions can be taken to strengthen the hospitals’ responses to the disasters. However, the proposed model should be validated in a hospital setting through implementation.Keywords: hospital, disaster, risk management, evaluation, model